2015
DOI: 10.7205/milmed-d-14-00363
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Biophysiological Toughness: Sustaining Working Memory During Physical Exhaustion

Abstract: Recent evidence suggests that increased dehydroepiandrosterone sulfate (DHEAS), in combination with decreased cortisol levels have been correlated with enhanced performance outcomes in stressful military environments. This study was implemented to replicate these findings in a group of active duty Air Force members to provide information on the usefulness of these biomarkers indices in the training and operational environment. Seventeen active duty males participated in the 4 sessions of this study. Sessions 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…DHEA and DHEAS appear to counteract the negative effects of increased cortisol on working memory function in women and men, respectively (315, 316). A dose-dependent inverted U-shaped response to DHEAS is observed on tests of learning and memory function in male mice (30).…”
Section: The Role Of Neurosteroids In Memory Deficits Associated Withmentioning
confidence: 99%
“…DHEA and DHEAS appear to counteract the negative effects of increased cortisol on working memory function in women and men, respectively (315, 316). A dose-dependent inverted U-shaped response to DHEAS is observed on tests of learning and memory function in male mice (30).…”
Section: The Role Of Neurosteroids In Memory Deficits Associated Withmentioning
confidence: 99%
“…In a recent meta-analysis, acute physical activity was reported to improve cognition when intensity is light to moderate, but when the activity is reported as hard to maximal, no benefit is observed (Chang, Labban, Gapin, & Etnier, 2012). Working memory accuracy was facilitated by physical exertion for the first 21 min of an incremental treadmill protocol, after which there was no difference to baseline (Shia et al, 2015). Pre to post the treadmill protocol, reaction time on a vigilance task was 6% slower (Shia et al, 2015), as well as 7% slower following a 2-hr treadmill march (Eddy et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Working memory accuracy was facilitated by physical exertion for the first 21 min of an incremental treadmill protocol, after which there was no difference to baseline (Shia et al, 2015). Pre to post the treadmill protocol, reaction time on a vigilance task was 6% slower (Shia et al, 2015), as well as 7% slower following a 2-hr treadmill march (Eddy et al, 2015). Following a 6.5-hr treadmill march, working memory accuracy was 7% worse and sensitivity on a vigilance task, calculated as z (hit rate) – z (false alarm rate), was ~20% lower (Bonnet, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…The same research group observed similar HRV relationships in naval cadets, but also demonstrated an association between cortisol levels and cognitive performance (Johnsen et al, 2012). In a study by Shia et al (2015), prolonged cortisol responses were also negatively associated with working memory, with DHEA-S:cortisol ratio demonstrating the potential to indicate resilient individuals. Whilst caveats to the research exist (e.g., dichotomous HRV groupings), collectively these biomarkers demonstrate potential.…”
Section: Introductionmentioning
confidence: 95%